Ensino de m??sica na escola: contribui????es para o desenvolvimento integral do ser humano - Figueiredo, Queila Garcia Moreno Sanches (2017)
This work aimed to investigate the contributions to the integral development of the human being that the teaching of music in the school provides. We seek in the first chapter to conceptualize the meaning of music and its characteristics as an artistic language. We emphasize the importance of music education in the different levels of Basic Education including its contributions in the three levels: Infant Education, Elementary Education and Secondary Education. In the second chapter we recorded through a brief history the teaching of music in Brazil highlighting the current legislation and the relevant facts that promoted and affirmed this teaching, among them Law 11.769 / 2008 and the movements and actions that contributed to its elaboration and promulgation. We have also commented on some facts that make law enforcement unfeasible, such as the lack of infrastructure of the schools and the lack of preparation of the majority of managers and teachers for this teaching. The new Law 13,278 / 16 changes the article of LDB 9394/96 that deals with music as a compulsory curricular component within the discipline of Art and adds the teaching of the other languages that compose it: visual arts, dance and theater. We also deal here with the National Directives for the Operationalization of Music Teaching and their indications for school praxis. In order to go further than just complying with a law, in the third chapter, we discuss the contributions that the teaching of music promotes in the integral development of the human being influencing the development of neurons and other cognitive, emotional, sensorial, intellectual, etc. actions. , Essential for the acquisition of learning. In the fourth chapter we report some successful experiences of teaching music in school through two educational proposals: Waldorf Schools and the Education Secretariat of Mogi das Cruzes. We have also brought some observations from experiences in my school practice. In the end, we make our considerations on the proposed subject, understanding that it is not exhausted here, but it convinces us that the teaching of music in school contributes greatly to the learning of everyone, both children and young people and adults, and it becomes an excellent Instrument for professionals working in this area.